Effect of layout and working fluid on heat transfer of polymeric shell and tube heat exchangers for small size geothermal ORC via 1-D numerical analysis. (September 2021) - Ceglia, F.; Marrasso, E.; Roselli, C.; Sasso, M.
Highlights: Enhancement of low-medium temperature geothermal use for polygenerative application. Analysis of alternative plastic material for heat exchanger in geothermal fields. Small size application of Organic Rankine Cycle. Economic feasibility of ORC in geothermal field. One dimensional design of shell and tube heat exchanger. Abstract: The geothermal energy is widely diffused in high size thermoelectric application by using high temperature sources. A high share of geothermal reservoirs is available worldwide in low-medium temperature and it is exploited only for thermal scopes. The use of low-medium enthalpy geothermal sources could be improved by considering the installation of small size power plant in fragmentary and poorly exploited geothermal sites providing power only or heat and power by using Organic Ranking Cycles technology. In order to reduce the cost of these typologies of geothermal power plant a strategy is here proposed to make them commercially attractive. In addition to drilling cost, a further element such as the corrosion issue strongly affects the economic analysis leading to the use of expensive components realized with high resistance materials that need to be frequently cleaned and/or replaced. The exploitation of low-medium temperature geothermal sources could be enhanced by using innovate cheaper materials for heat exchanger allowing the direct interaction between working fluid and geothermal brine, appropriately treated, taken by the aquifer. The present work aims to analyse the use of a polymer-based evaporator in a 10 kWel Organic Rankine Cycle system to overcome the fouling problem due to geothermal fluid. A detailed analysis with two different layouts for a shell and tube heat exchanger, by considering the combination of five different working fluids, by comparing three polymers with two commonly used metals, has been conducted. This analysis has been carried out with a one-dimensional mathematical approach including the evaluation of heat exchange coefficients and pressure drops by using the correlation available in the scientific literature for each possible combination of fluid-material-layout. The outcomes provide the energy and economic analysis for the shell and tube heat exchanger considering the design characteristic of modelled ORC system. The results have demonstrated that the higher performance will be obtained if the working fluid is in the tubes side. The best combination of fluid, layout and polymer leads to a cost saving of evaporator of 73% with respect to titanium on the basis of the same life cycle time. Graphical abstract: Image, graphical abstract